Unregulated high seas fisheries: the interlopers issue - Coelho, M. P.; Filipe, J.; Ferreira, M. A. M. (Working Papers nº 43 / 2015 OBEGEF – Observatório de Economia e Gestão de Fraude, 2015)
Illegal behaviour and public enforcement of law are important theoretical and empirical subjects for Economics. They were dormant in economic scholarship, until the article of Becker, 1968, “Crime and Punishment: An Economic Approach”. In the context of Fisheries Economics, the problem can be seen as an externality arising when exclusive property rights are absent. That absence depends on the costs of defining and enforcing exclusivity and the problem becomes more complex when fisheries are transboundary. The paper combines standard Economics of Fisheries analysis with the Theory of “Crime and Punishment”. The conclusions are used to discuss the so-called issue of “interlopers” in High Sea fisheries. The “unfinished business” of the Law of the Sea, that is, the imprecise definition of property rights in the areas of High Sea adjacent to Economic Exclusive Zones, were in the origin of a lot of “fish wars” in the nineties. The 1995 UN agreement on transboundary stocks and highly migratory species pretended to be a new form of cooperation, including the introduction of new forms of enforcement and compliance with the law, affecting fishing enterprises and convenience-flag vessels. However, with the legal procedures that were proposed, it seems broadly bounded, the potential effect of enforcement and regulation.